Validation of cleaning procedures used in an Italian Hospital Pharmacy for antineoplastic drug decontamination: a new tool for industrial hygiene: Validation of cleaning procedures of antineoplastic drugs - Negri, Sara; Oddone, Enrico; Morandi, Francesco; Sottani, Cristina; Gardinali, Francesco; Lillo, Annalisa; Pastoris, Ornella; Dacrema, Valerio; Losurdo, Anna; Grignani, Elena; Cottica, Danilo; imbriani, Marcello (La Medicina del Lavoro, 2019)
Background: Current Italian regulations and procedures for surface decontamination of antineoplastic drugs (ADs) are not clear. Therefore, most hospital pharmacies follow internal procedures as an interpretation of the recommended handling guidelines. Objectives: Our study compared 7 different cleaning procedures after controlled contamination of the work surface of a biological safety cabinet workbench in an Italian hospital oncology pharmacy (HOP) to determine which of them is more efficient and practical. Moreover, in order to approximate operative routine and improve risk awareness, cleaning procedures were carried out by the personnel that usually operate in the HOP. Methods: Measured quantities, i.e. a drop (100 μL) of 5-FluoroUracil, IPhosfamide, CycloPhosphamide and Gemcitabine, were deposited on the work surface within precisely delimited areas. Following the wipe-test analysis using UPLC-MS/MS, the cleaning efficacy was calculated based on the ratio of the residual concentration of the AD, after the cleaning procedure, to the concentration of each AD before the procedure. Results: Tested cleaning procedures were: 1) Hypo-Chlor®, hot water and Farmecol70®; 2) Hypo-Chlor® and hot water; 3) Farmecol70®; 4) Surfa’Safe SH® and hot water; 5) Amuchina® 10%, hot water and Farmecol70®; 6) Incidin® Oxyfoam and hot water; 7) liquid Marseille soap, hot water and Farmecol70®. Within the studied HOP, the Marseille soap was evaluated to be the optimal choice due to its efficacy, low cost, and the very short contact time needed before rinsing. Discussion: The application of the protocol for procedure validation suggested here could be used in every HOP as a reliable industrial hygiene tool to demonstrate the validity of the chosen cleaning procedure.